2019
DOI: 10.4103/sja.sja_766_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ultrasound-guided versus conventional palpatory method of dorsalis pedis artery cannulation: A randomized controlled trial

Abstract: Background:Whether use of ultrasound (USG) to cannulate dorsalis pedis artery (DPA) increases first pass successful cannulation, decreases the number of attempts and complications as compared to palpation technique was assessed in this study.Design:Randomized controlled trial.Setting:Operating room.Patients:About 60 adult patients undergoing any head–neck or faciomaxillary surgery requiring arterial cannulation were enrolled.Intervention:DPA was cannulated either by USG-guided technique (USG group) or by palpa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Various studies have shown that USG guidance for vascular access has decreased rate of failure and incidence of complications. [ 3 4 5 ] Studies have shown that using classical Seldinger or modified Seldinger technique (Dart) have increased success rate of arterial cannulation as compared to Direct technique. [ 2 ] Avoidance of impingement of needle tip on posterior wall has been cited for better results with these techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown that USG guidance for vascular access has decreased rate of failure and incidence of complications. [ 3 4 5 ] Studies have shown that using classical Seldinger or modified Seldinger technique (Dart) have increased success rate of arterial cannulation as compared to Direct technique. [ 2 ] Avoidance of impingement of needle tip on posterior wall has been cited for better results with these techniques.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Ultrasound-guided radial arterial cannulation has been found to be associated with increased first pass success rate (76.7%) in comparison to palpation method (60%). [ 3 ] To our knowledge, the comparison of two different techniques of arterial cannulation (Direct and Dart) has never been conducted by ultrasound guidance. In this study, it was aimed to compare the rate of successful cannulation within 5 min.…”
Section: Introductionmentioning
confidence: 99%
“…DPA is the choice of AC for patients when the radial artery is inaccessible. [ 1 ] The AC is a painful procedure that worsens by repeated attempts to cannulate the artery. [ 2 3 ] The local lignocaine infiltration on the dorsal surface of the foot is the commonly employed technique for procedural pain relief during DPA cannulation, but the drug infiltration itself causes discomfort and provides a limited area of analgesia.…”
mentioning
confidence: 99%
“…The lidocaine infiltration (LI), topical lidocaine cream, and ethyl chloride spray are reported methods in the literature for pain management during AC. [ 1 2 3 ] The topical application carries the drawback of slower onset of action, expensive, and reduced efficacy than LI. [ 2 ] The subcutaneous LI around the arterial puncture site carries significant discomfort.…”
mentioning
confidence: 99%
“…7 The use of ultrasound guidance is a well-validated adjunct to cannula insertion and is gaining popularity due to its reduced cannula failure rate. 8 The advantages of ultrasound guidance include real-time visualization, better pre-procedure planning, and reduction of catheter-related infections due to reduced trial and increased first-trial success. 9 Major surgery is surgery of long duration, organ ischemia, blood loss of more than 1000 mL, high use of vasopressors, and postoperative metabolic stress response.…”
mentioning
confidence: 99%